Does the London Metal Exchange follow a random walk? Evidence from the predictability of futures prices - Sascha Otto (The Open Economics Journal, 2010)
This paper analyses the validity of the weak-form market efficiency, using the random-walk hypothesis for the six industrial base metals - copper, aluminium, zinc, nickel, tin and lead - traded at the London Metal Exchange. I analyse the behaviour of daily and weekly prices of the daily rolling three-month futures contracts, as these contracts exhibit the highest level of trading activity. In contrast to other efficient-market studies, the efficiency of futures prices is not tested as an unbiased predictor of the spot prices but from the predictability of futures prices themselves. I focus on the post-Tin Crisis period of 1989 to 2007. My test methodology includes the Box & Pierce Q-statistics, variance ratio tests by Lo and MacKinlay with homoscedastic and heteroscedastic test estimates, nonparametric ranks- and signs-based variance ratio tests by Wright and wild bootstrapping variance ratio tests by Kim. My sample basis fails to reject the random-walk hypothesis for all base metal futures except for lead.
Keywords: 330; London Metal Exchange; LME; random walk; weak-form efficiency; futures markets; commodities